Atlantic Ocean CO2 uptake reduced by weakening of the meridional overturning circulation. - Pérez, Fiz F.; Mercier, Herlé; Vázquez-Rodríguez, Marcos; Lherminier, Pascale; Velo, Anton; Pardo, Paula C.; Rosón, Gabriel; F. Ríos, Aida (Nature Geoscience, 2013)
International audience Uptake of atmospheric carbon dioxide in the subpolar North Atlantic Ocean declined rapidly between 1990 and 2006. This reduction in carbon dioxide uptake was related to warming at the sea surface, which--according to model simulations--coincided with a reduction in the Atlantic meridional overturning circulation. The extent to which the slowdown of this circulation system--which transports warm surface waters to the northern high latitudes, and cool deep waters south--contributed to the reduction in carbon uptake has remained uncertain. Here, we use data on the oceanic transport of volume, heat and carbon dioxide to track carbon dioxide uptake in the subtropical and subpolar regions of the North Atlantic Ocean over the past two decades. We separate anthropogenic carbon from natural carbon by assuming that the latter corresponds to a pre-industrial atmosphere, whereas the remaining is anthropogenic. We find that the uptake of anthropogenic carbon dioxide--released by human activities--occurred almost exclusively in the subtropical gyre. In contrast, natural carbon dioxide uptake--which results from natural Earth system processes--dominated in the subpolar gyre. We attribute the weakening of contemporary carbon dioxide uptake in the subpolar North Atlantic to a reduction in the natural component. We show that the slowdown of the meridional overturning circulation was largely responsible for the reduction in carbon uptake, through a reduction of oceanic heat loss to the atmosphere, and for the concomitant decline in anthropogenic CO2 storage in subpolar waters.